PHOTOCHEMICAL STUDY OF TRIS(ETHYLXANTHATO) IRON(III) IN DIFFERENT ORGANIC SOLVENTS - Shalan, Nasser (Al-Nahrain Journal of Science, 2018)
The photochemistry of Tris(ethylxanthato) iron(III) was studied in five organic solvents: dimethyl sulfoxide (DMSO), methanol, acetone, ethyl acetate and Benzene .Monochromatic light of wavelength 365 nm was used for the irradiation process at 25 oC. Uv-visible spectral changes and other observations indicated an intra oxidation-reduction reaction occuring during the photolysis of Fe(etx)3 complex, with homolytic scission of Fe-S bond. The quantum yield (d), rate of photodecomption and reactivity ratio (k2/k-1) were determined in each solvent. These values always increase as the polarity of the solvent increased and following the order.DMSO > Methanol > Acetone > Ethyl acetate > Benzene According to the experimental results obtained, the mechanism of photodecomption of these complexes under the applied conditions was proposed.